Analisis Kemampuan Pemecahan Masalah Matematis : Dampak Model Pembelajaran Reciprocal Teaching Dengan Fieldtrip - Darmani, Jamroni Wibi; Renaldi, Achi (Desimal: Jurnal Matematika, 2018)
Students' mathematical problem solving ability is very important. But the results of the observation and supported by several studies of students' mathematical problem solving abilities are still very low. It is suspected that reciprocal teaching learning model with the help of tripships can improve students' mathematical problem solving abilities. This study aims to determine the effect of using reciprocal teaching models with fieldtrips on students' mathematical problem solving abilities. The sampling technique used was cluster random sampling with 2 classes, namely experimental class (the class was treated with reciprocal teaching learning model with fieldtrip), and the control class (the class was treated by conventional models). The hypothesis test used is the t-test. The results of the study found that there were differences in students 'mathematical problem solving abilities using reciprocal eaching learning models with fieldtrips on students' mathematical problem solving abilities. Furthermore, the mathematical problem solving ability of students with reciprocal teaching learning model is better than the students' mathematical problem solving abilities using conventional learning models. The conclusion of this study is that there is influence in improving students' mathematical problem solving ability by using reciprocal teaching learning model with fieldtrip to.